Computer-assisted generalized partial linear models - Marlene Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
A particular semiparametric model of interest is the generalized partial linear model (GPLM) which allows a nonparametric modeling of the influence of the continuous covariables. The paper reviews different estimation procedures based on kernel methods and test procedures on the correct specification of this model (vs. a parametric generalized linear model). Simulations and an application to a data set on East-West German migration illustrate similarities and dissimilarities of the estimators and test statistics. Semiparametric methods are highly demanding on software. Thus the presentation is completed by indicating the practical implementation in new version of the statistical computing environment XploRe.
urn:nbn:de:kobv:11-10064280
Keywords: 330